Physicochemical quality of beef sausage with the substitution of tapioca flour and kepok banana flour (Musa paradisiacal formatypica) - Mukhlisah, Andi Nurul; Dwi Ningtyas, Weny; Irfan, Muhammad; Syah, Setiawan Putra (Politeknik Negeri Jember, 2024)
This study aimed to evaluate the physicochemical quality of beef sausage made by replacing tapioca flour as an essential filler in sausage making with kepok banana flour. This study used a 4 × 5 randomized complete block design (CRD) pattern with a total of 20 experimental units. The variables tested included amylose, amylopectin, water holding capacity, hardness, and pH of the sausage. Data were analyzed using analysis of variance with SPSS 16 software and further tested using Duncan's method to see differences between treatments. The results showed that the amylose content of sausages ranged from 0.33±0.04 to 0.57±0.01%; amylopectin content ranged from 3.83±0.15 to 3.29±0.10%; water holding capacity ranged from 30.67±9.86 to 48.11±5.74%; pH ranged from 4.29±0.02 to 6.31±0.15, and hardness ranged from 1,271.5±56.8 to 2,261.75±71.7 g. The F3 treatment yielded the best results. The best results were shown in treatment F3 (15% kepok banana flour + 5% tapioca). The use of banana flour, up to 15% as a substitute for tapioca flour, can be used in making beef sausage.